Pengaruh Latihan Ladder Drill Two Feet Step Dan Latihan Ladder Drill Icky Shuffle Terhadap Kelincahan Pemain Futsal SMA Negeri 5 Purworejo - Rezkya Wahyu Aulia; Mohammad Annas; Mugiyo Hartono; Moch Fahmi Abdulaziz (Indonesian Journal for Physical Education and Sport, 2024)
Lack of mastery of agility is the cause of decreased achievement in male futsal players of SMA Negeri 5 Purworejo. The purpose of this study was to determine the effect of training Ladder drill two feet step and Ladder drill icky shuffle on the agility of male futsal players SMA Negeri 5 Purworejo. This research uses quantitative research with experimental design using ‘two groups pretest-posttest design. The results of data analysis are the influence of the effect of training ladder drill two feet step and ladder icky shuffle on the agility of male futsal players SMA Negeri 5 Purworejo at the level of Sig < 0.05 and t count> t table. Ladder drill icky shuffle training is more significant in improving agility than Ladder drill two feet step training with a difference of 3.99% increase in agility. The conclusion of this study is that agility training with the Ladder drill two feet step training method and Ladder drill icky shuffle training has an effect on increasing the Male Futsal Players of SMA Negeri 5 Purworejo Year 2024. Ladder drill icky shuffle exercise is more significant than Ladder drill two feet step in improving agility in Male Futsal Players of SMA Negeri 5 Purworejo Year 2024